Synthesis, Molecular Docking, Anti-cholinesterase Activity, Theoretical Investigation, and Catalytic Effect of New Encumbered N-benzyladamantyl Substituted Imidazolidin-2-ylidene Carbene Pd-PEPPSI Complexes - Ikhlef, Sofiane; Lasmari, Sarra; Zendaoui, Saber M.; Mokrani, El Hassen; Tebbani, Dahmane; Gürbüz, Nevin; Bensouici, Chawki; Boulcina, Raouf; Zouchoune, Bachir; Özdemir, Ismail (Current Organic Chemistry, 2024)
This study aimed to describe the preparation of novel PEPPSI type Pd(II)-NHC complexes bearing N-benzyladamantyl substituted imidazolidin-2-ylidene group. All synthesized compounds were characterized by using 1H-NMR and 13C-NMR spectroscopies, FTIR, and elemental analysis techniques. One of the objectives of this study was the synthesis of Pd-NHC complexes with AChE/BChE inhibition activities. Among all the tested compounds, complexes 4b and 4c were found to have the most high potential AChE and BChE inhibitory activities with IC50 values of 21.57 ± 0.23 Mm and 15.78 ± 0.39 Mm, respectively. Conducting molecular docking studies helped us in gathering crucial information about the main binding interactions of inhibitors and enzymes, and the results were in agreement with the biological evaluation. The synthesized Pd-NHC complexes were employed for catalyzing the direct C2- and C5-arylation reaction between aryl (hetero) halide and a variety of heterocyclic systems. In both cases (C2 and C5-arylation), Pd-NHC complexes catalysts provided access to the arylated heterocycles in good to high yields in the presence of 1 mol% catalyst loading at 150°C. The DFT theoretical investigation showed that the Pd-NHC complexes were of ML2X2 type, where the the Pd(II) cation had a square planar geometry. The interaction energies obtained by energy decomposition analysis (EDA) demonstrated that the 4d and 4e complexes were more stable in the presence of more methyl substituents. The chemical indicators demonstrated that the less stable 4c complex was more reactive in regard to the chemical hardness, chemical potential, and electrophilicity values.
Keywords: N-Heterocyclic carbenes